Tunable diacetylene polymerized shell microbubbles as ultrasound contrast agents - Park, Y; Luce, A; Whitaker, R; Amin, B; Cabodi, M; Nap, R; Szleifer, I; Cleveland, R; Nagy, J; Wong, J (2012)
Monodisperse gas microbubbles, encapsulated with a shell of photopolymerizable diacetylene lipids and phospholipids, were produced by microfluidic flow focusing, for use as ultrasound contrast agents. The stability of the polymerized shell microbubbles against both aggregation and gas dissolution under physiological conditions was studied. Polyethylene glycol (PEG) 5000, which was attached to the diacetylene lipids, was predicted by molecular theory to provide more steric hindrance against aggregation than PEG 2000, and this was confirmed experimentally. The polymerized shell microbubbles were found to have higher shell-resistance than nonpolymerizable shell microbubbles and commercially available microbubbles (Vevo MicroMarker). The acoustic stability under 7.5 MHz ultrasound insonation was significantly greater than that for the two comparison microbubbles. The acoustic stability was tunable by varying the amount of diacetylene lipid. Thus, our polymerized shell microbubbles are a promising platform for ultrasound contrast agents. © 2012 American Chemical Society.